The effects of nosocomial rotavirus gastroenteritis on the length of hospital stay and cost - Gundeslioglu, Özlem O; Tekin, Recep; Cevik, Saliha; Palancı, Yılmaz; Yazıcıoglu, Atilla (The Journal of Infection in Developing Countries, 2016)
Introduction: In this study, the goal was to evaluate the impact of nosocomial rotavirus gastroenteritis in pediatric patients by determining the incidence of nosocomial rotavirus gastroenteritis, the resulting duration of hospital stay, and direct cost. To our knowledge, this is the first study in Turkey that evaluates the impact of pediatric nosocomial rotavirus gastroenteritis on duration of hospital stay and calculates the direct cost. Methodology: Forty-nine patients who were diagnosed with nosocomial rotavirus gastroenteritis and hospitalized were included in the study. Nosocomial infection rates, organ systems affected by the nosocomial infections, and patients who had nosocomial rotavirus gastroenteritis were identified. A direct cost analysis of patients who were diagnosed with nosocomial rotavirus gastroenteritis was performed using copies of the invoices for the hospital bills. Results: During the study period, there were 49 cases of nosocomial rotavirus gastroenteritis. The length of hospitalization was extended, on average, by more than 6.3 days in cases of nosocomial rotavirus gastroenteritis. The cost of hospitalization for patients with nosocomial rotavirus gastroenteritis was on average 1,554 ± 2,067 US dollars, compared to a cost of only 244 ± 103 US dollars for patients who did not have nosocomial rotavirus gastroenteritis. This difference in cost was statistically significant (p < 0.05). Conclusions: Nosocomial rotavirus gastroenteritis is important because it significantly prolongs hospital stay and increases the social and economic burden of the hospitalization. Nosocomial rotavirus gastroenteritis can be reduced with prevention measures such as handwashing, isolation, and cohorting.